Stable pelvic floor muscle training improves urinary incontinence in women with gestational diabetes mellitus - Yingying Wu; Tingting Li; Fengcheng Cai; Xinru Ye; Mengyan Xu (Journal of Obstetrics and Gynaecology)
Background Gestational diabetes mellitus (GDM) is a common metabolic disease that contributes to urinary incontinence (UI) in pregnant women. The aim of this study was to investigate the therapeutic potential of stable pelvic floor muscle (PFM) training with transverse abdominal muscle for pregnancy-specific UI in patients with GDM.Methods This was a randomised controlled trial. A total of 73 pregnant women with GDM and pregnancy-specific UI were screened, 35 of whom received stable PFM training with transverse abdominal muscle in the second trimester. After six weeks of training, UI status was assessed by the quantity of fluid loss and the International Consultation on Incontinence Questionnaire short form (ICI-Q-SF), and the quality of life was evaluated by the Incontinence Quality of Life Questionnaire score. Additionally, the thickness of the transverse abdominal muscle was measured by ultrasonography.Results At 6 weeks later, the quantity of fluid loss and ICI-Q-SF score were significantly lower, and the overall healing rate was significantly higher in the training group than those in the control group. The training also significantly improved the quality of life, especially in terms of behavioural limitation and psychosocial impact. Additionally, the thickness of transverse abdominal muscle under the status of maximal contractions of transverse abdominal muscle and PFM was significantly higher in the training group than in the control group after 6 weeks.Conclusions Stable PMF training with transverse abdominal muscle alleviated UI and improved the quality of life in patients with GDM. The thickening of transverse abdominal muscle induced by the training contributes to the remission of UI through the cooperation of PMF.